APICAL SPIKELET ABORTION (ASA) Controls Apical Panicle Development in Rice by Regulating Salicylic Acid Biosynthesis - Zhou, Dan; Shen, Weifeng; Cui, Yuchao; Liu, Yuqin; Zheng, Xijun; Li, Yan; Wu, Minliang; Fang, Shanru; Liu, Chunhong; Tang, Ming; Yi, Yin; Zhao, Mingfu; et al. (Frontiers in Plant Science, 2021)
Panicle degradation after abiotic stress causes severe yield reduction in rice. There are two main types of panicle degradation: apical spikelet abortion and basal degeneration. In this study, we isolated and characterized the apical panicle abortion mutant apical spikelet abortion (asa), which exhibits degeneration and defects in the apical spikelets. This mutant had a pleiotropic phenotype, characterized by reduced plant height, increased tiller number, and decreased pollen fertility. Map-based cloning revealed that OsASA encodes a boric acid channel protein that showed the highest expression in the inflorescence, peduncle, and anther. RNA-seq analysis of the asa mutant vs wildtype (WT) plants revealed that biological processes related to reactive oxygen species (ROS) homeostasis and salicylic acid (SA) metabolism were significantly affected. Furthermore, the asa mutants had an increased SA level and H2O2 accumulation in the young panicles compared to the WT plants. Moreover, the SA level and the expression of OsPAL3, OsPAL4 and OsPAL6 genes (related to SA biosynthesis) were significantly increased under boron-deficient conditions in the asa mutant and in OsASA-knockout plants. Collectively, these results suggest that the boron distribution maintained by OsASA is required for normal panicle development in a process that involves modulating ROS homeostasis and SA biosynthesis.